The feasibility of a randomised controlled trial to compare the cost-effectiveness of palliative cardiology or usual care in people with advanced heart failure: Two exploratory prospective cohorts. (June 2018) - Johnson, Miriam J; McSkimming, Paula; McConnachie, Alex; Geue, Claudia; Millerick, Yvonne; Briggs, Andrew; Hogg, Karen
Background: The effectiveness of cardiology-led palliative care is unknown; we have insufficient information to conduct a full trial. Aim: To assess the feasibility (recruitment/retention, data quality, variability/sample size estimation, safety) of a clinical trial of palliative cardiology effectiveness. Design: Non-randomised feasibility. Setting/participants: Unmatched symptomatic heart failure patients on optimal cardiac treatment from (1) cardiology-led palliative service (caring together group) and (2) heart failure liaison service (usual care group). Outcomes/safety: Symptoms (Edmonton Symptom Assessment Scale), Kansas City Cardiomyopathy Questionnaire, performance, understanding of disease, anticipatory care planning, cost-effectiveness, survival and carer burden. Results: A total of 77 participants (caring together group = 43; usual care group = 34) were enrolled (53% men; mean age 77 years (33–100)). The caring together group scored worse in Edmonton Symptom Assessment Scale (43.5 vs 35.2) and Kansas City Cardiomyopathy Questionnaire (35.4 vs 39.9). The caring together group had a lower consent/screen ratio (1:1.7 vs 1: 2.8) and few died before approach (0.08% vs 16%) or declined invitation (17% vs 37%). Data quality: At 4 months, 74% in the caring together group and 71% in the usual care group provided data. Most attrition was due to death or deterioration. Data quality in self-report measures was otherwise good. Safety: There was no difference in survival. Symptoms and quality of life improved in both groups. A future trial requires 141 (202 allowing 30% attrition) to detect a minimal clinical difference (1 point) in Edmonton Symptom Assessment Scale score for breathlessness (80% power). More participants (176; 252 allowing 30% attrition) are needed to detect a 10.5 change in Kansas City Cardiomyopathy Questionnaire score (80% power; minimum clinical difference = 5). Conclusion: A trial to test the clinical effectiveness (improvement in breathlessness) of cardiology-led palliative care is feasible.